Extraire plus pour sauvegarder la planète ? Justifications d’un projet minier de la transition énergétique - Axelle Ferrant (VertigO, 2023)
New critical and strategic mineral extraction projects are emerging around the world to support the growing demand for minerals that are presented as necessary for the transition to 'green' energy and for the climate change mitigation. These projects are controversial and bring together or oppose stakeholders around different values. This paper contributes to the debate on the contradictory nature of climate change strategies that rely on the intensification of mineral resource extraction. More specifically, it examines the justifications used by industry, government and civil society actors to influence the legitimacy of a transition mining project. Based on a content analysis of press articles related to a controversial lithium mine project in Quebec, the article mobilizes Boltanski and Thévenot's (1991) theory of the economies of worth to account for the grammars of justification used by the various stakeholders. The results indicate that the controversy crystallizes around two aspects of the civic world. The energy transition is not discussed in the public discourse on the project studied. The techno-centric and interventionist vision of the transition, as Audet defines it (2016), is locked into the operationalization of the transition as defined by the public authorities, without allowing other alternatives to emerge in the debates around a mining project of the transition. The article contributes to the discussions on the need to open spaces for dialogue around these projects to collectively define the possible trajectories of the transition.